2020
DOI: 10.18697/ajfand.89.18645
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the women’s development team leaders in delivering nutrition education on pulse sprouting in Southern Ethiopia

Abstract: Effectively implemented nutrition education can provide participants with the knowledge and skills to make healthy food choices in the context of their lifestyles and economic resources. In Ethiopia, the government equips health extension workers (HEWs) to provide nutrition education to communities by enabling HEWs to transfer knowledge to women's development team leaders (WDTLs) who in turn share the knowledge with the one-to-five network leaders (1-5NWL) and members. The objective of this study was to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Germination is an indigenous food processing method [ 44 ] used in Ethiopia [ 45 ] but with a low rate of use for complementary foods. This holds for our study and Southern Ethiopia [ 46 ]. Key to its acceptability, religious leaders and HDA leaders favoured germinated grain flour to improve complementary foods.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Germination is an indigenous food processing method [ 44 ] used in Ethiopia [ 45 ] but with a low rate of use for complementary foods. This holds for our study and Southern Ethiopia [ 46 ]. Key to its acceptability, religious leaders and HDA leaders favoured germinated grain flour to improve complementary foods.…”
Section: Discussionsupporting
confidence: 67%
“…The productivity of community health workers such as HEWs and HDA leaders depends on knowledge and skills, motivation, and their work environment (supportive supervision and workload) [ 56 ]. In this regard, unlike Mulualem et al [ 50 ] and other studies [ 20 , 21 , 29 , 30 , 46 , 50 , 51 ] that examined ARF use in complementary foods using existing health delivery platforms, our study has reported opportunities and challenges surrounding ARF implementation from HDA leaders’ perspectives.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations